Employing organizational value dimensions to enhance the reputation of organizations - Al-Hamad, Alaa Daham; 'Abdel-Mawgoud, Ala (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to test the relationship and influence of organizational values in the reputation of organizations in the Baghdad Provincial Council, and then try to come up with a set of recommendations that contribute to strengthening the organizational values of the researched organization. The descriptive analytical approach was adopted in carrying out this research and data was collected from (40) respondents who represent the research community exclusively In full, by adopting the questionnaire consisting of (36) paragraphs, the research adopted (Spss V.24) program with the adoption of descriptive statistics methods (linearity test, natural distribution test, confirmatory factor analysis, arithmetic mean, percentages, standard deviation, relative importance, coefficient of variation, The regression coefficient b Mediator) to test his hypotheses. The most prominent research findings are embodied.